Macroscopic, Histological, and Microbiological Characterization of Contact Lesions at the Tibiotarsal Region of Broilers - Cavani, Ricardo [UNESP]; Da Silva Rubio, Marcela [UNESP]; Alves, Khauston Augusto Pereira; Pizauro, Lucas José Luduverio [UNESP]; Cardozo, Marita Vedovelli; Silva, Paulo Lourenço; Silva, Iran José Oliveira; Avila, Fernando Antônio [UNESP] (Springer Nature, 2022)
Brazil is considered as a great broiler feet exporter, especially for the Chinese trade. Contact lesions at the tibiotarsal region are responsible for economic losses and there is no model for its classification, thereby this study presents a fast and practical grade system to be used in the poultry industry and proposes these lesion characterizations into three different grades. For this, correlation was made between macroscopic, histological findings and microbiological quantification (Escherichia coli, Staphylococcus spp., Streptococcus spp. and sulphite-reducing clostridia) from contact lesions in the tibiotarsal region of 112 broiler carcasses, divided in four groups (n=28), accordingly to the lesion's intensity. There were no significant differences in microbiological quantification among the groups (p>0.05) except for the grade 3 group, as grade 1 and 2 lesions were in the early stages and histopathological changes such as ulceration were not observed. In grade 3 lesion group, it was observed bacterial cocci grume and ulceration at the articular region and significantly higher microbiological count (p<0.05) for E. coli and Staphylococcus spp. In conclusion, the visual standard proposed in this work, correlated and confirmed by the histopathologic, and microbiologic characterization, allows to precise and fast ascertainment of the contact lesion grade in the tibiotarsal regions of broiler carcasses. Moreover, it should be highlighted that grades 1 and 2 alterations are not caused by an inflammatory process caused by pathogenic agents and should not be considered a public health risk.
Keywords: carcass condemnation; dermatitis; Hock burn; inspection line; slaughterhouse